ENT300 Fundamental of Entrepreneurship. Business Plan : Bubble Shines House Cleaning Services / Verona Ramas Anak Joseph...[et.al] - Joseph, Verona Ramas; Wan Abd. Hamid, Sh. Hazirah Faiqah; Thomson, Stephalce Jane; Tingom, Jeff; Azmi, Mohamad Norazwan (2015)
Bubble Shines House Cleaning Services is a company that provides a specific type of house cleaning services which is custom made to its customer’s desire. Our business is in form of enterprise which consists of five members whereby the entire member gives full support to this project. House cleaning services has a high potential in making high profit. In fact, a lot of people do not have time to manage and cleaning their house as they are busy in daily life and thus cleaning has been high in demand. This company will help them by providing cleaning services which is affordable to our client. The specialty of this company is that we provide special services during our customer’s birthday which we provide free cleaning services for that day when they have registered to be the members of this company. In the future, our target is to be the number one house cleaning services that are preferred by most citizens in Malaysia and have at least one branch in all states in Malaysia.